(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
International Red Cross and Red Crescent Movement - Brief itinerary- From Henry Dunant, Pioneer of the Red Cross to the Proximity of our Days. The International Red Cross and Red Crescent Movement is an international humanitarian organization whose sacred mission is to protect the life and health of people, to ensure respect for the human being, to prevent and alleviate the suffering of fellow human beings, a performance that will not suffer discriminatory influences regardless of nationality, race, religion, gender, social class, cultural or political opinions. The movement consists of several distinct institutions, legally independent, but united within the same system engaging and interacting with each other through common basic principles, objectives, symbols, statutes and governing bodies, as follows: International Committee of the Red Cross, International Federation of Red Cross and Red Crescent Societies, National Red Cross and Red Crescent Societies. The article in question aims to familiarize with these institutions, the history and the promotion of the principles that govern their operation and collaboration, and implicitly preserve the homo sapiens dignity and integrity.